Fake News and Its Implications for Sustainable Development Goals in Delta State - Hannah Emuobosa Ivwighren; Oghenetejiri Valeria Mukoro (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
This paper focuses on the implications of fake news for the realization of the Sustainable Development Goals (SDGs) in Delta State, Nigeria. This issue has progressively interfered with health communication, education programs, and peace-building efforts, as well as with trust in institutions. The objective aims to align the core of SDGs 3, 4, and 16 regarding how they are interpreted and applied to development. A mixed-methods design was adopted, using a survey and key informant interviews. A sample of 400 was collected for quantitative data, and 18 key informant interviews were conducted for qualitative data. The findings, analysed using descriptive statistics, correlation, and regression, show a significant negative association with exposure to fake news. Thematic analysis of the interview data showed that the dissemination of fake news is primarily driven by social media, which erodes people’s trust. The study concludes that fake news is a serious challenge to sustainable development in Delta State. It recommends intensifying media literacy and improving open communication to reduce the effects of misinformation on the achievement of the SDGs.